Bitesize Product Development and Marketing Innovation in Tempeh Chips Food SMEs - Intan Shaferi; Alisa Tri Nawarini; Rio Dhani Laksana; Ary Yunanto (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Business development is part of the dynamics of economic activity which is increasingly developing along with the progress of the times. MSMEs run businesses independently in their economic activities. Therefore, creativity in developing a business is highly expected. One form of creativity is innovation. Chip products are traditional foods that have long been embedded in society. Tempeh chips with a savory and light taste to eat in box-shaped packaging. However, along with the rapid development of business, many are trying to provide a touch of variety in taste. However, it was not easy for the market to accept the change because the original taste was considered the best. With this phenomenon, it is hoped that MSMEs will have other ways to be creative and innovate. One of the MSMEs is tempeh chips in the South Purwokerto area. This MSME has been around for a long time and provides supplies to several other places. However, innovation needs to be carried out to have its own new and more profitable market because it has selling points that are more popular with the market. The method used in this program is to create a community service program in the form of innovating new product variations in the form of new tempeh in small sizes for selling value and initiating a marketing network to develop the business. So it is hoped that the knowledge possessed by academics can be useful for implementing science and technology to develop MSME businesses. The output of this program is small size tempeh chips products in packaging and marketing development.